A 3D scanning system for biomedical purposes. (29th June 2009) - Bradley, B.D.; Chan, A.D.C.; Hayes, M.J.D.
The use of three-dimensional (3D) scanning systems for acquiring the external shape features of biological objects has recently been gaining popularity in the biomedical field. A simple, low cost, 3D scanning system is presented, which employs the laser light-sectioning technique for data acquisition. A Direct Linear Transformation least squares algorithm is used for camera calibration and Elliptical Fourier Descriptors (EFDs) are used for data smoothing and planar section reconstruction. Results for an experiment demonstrating the validity of the EFD approach are presented. Overall, results presented for three objects scanned with the proposed system demonstrate the validity of the chosen approach. This is an expanded version of a paper presented at the 3rd IEEE International Workshop on Medical Measurements and Applications, 9?10 May 2008, Ottawa, ON, Canada.